OPTIMALISASI PEMBERANTASAN KORUPSI DI INDONESIA - Waluyo, Bambang (Jurnal Yuridis, 2014)
Operationalization of fighting corruption should be done in comprehensive, integral and holistic methods. Commitment of law enforcement with firm, consistent, and integrated is an important step to be able to produce a just law enforcement, providing legal certainty, and benefits to society. These steps can be taken through the imposition of the toughest sanctions for perpetrators of corruption, criminal sanctions, fines, restitution, reversed evidence accumulated with money laundering crime (MLC), accompanied by the provision of social sanction . This is expected to increase public confidence , investors , national pride , as well as a deterrent effect, preventing corrupt candidates, optimize the return on the state or the people's money and other pos itive impacts.